THE EFFECTIVENESS OF GODIGI SERVICES IN FACILITATING THE ISSUANCE OF E-KTP (STUDY AT THE POPULATION AND CIVIL REGISTRATION OFFICE OF PROBOLINGGO REGENCY) - Fariza Ghadavi; Supriyanto; Mastina Maksin (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study examines the effectiveness of services provided by the Probolinggo Regency Population and Civil Registration Office in the E-KTP making service. The focus of this study is based on P Sondang Siagian's effectiveness theory which consists of 3 indicators and to identify internal and external inhibiting factors in Probolinggo Regency through the GoDigital (GODIGI) online service. With this service, the public is given convenience in the process of submitting and making E-KTP online and can cut time and reduce long queues. With GODIGI, the public is given convenience in the process of making E-KTP, they can apply anywhere and anytime through online services with delivery via the post office. However, in practice in the field there are still inhibiting factors in the process of making E-KTP through the GODIGI online service. This study uses a qualitative approach with a purposive sampling data collection technique to select informants who truly understand and know about the GODIGI online service. Data were obtained through observation, interviews, and documentation in obtaining data in the field and analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that GODIGI online services using 3 indicators of effectiveness according to P Sondang Siagian have been running effectively through time factors, accuracy factors, and style factors. From the informant's response who has said that the presence of GODIGI is very helpful in the process of making E-KTP especially in cutting time and not having to queue at the office and the level of accuracy in obtaining input data and providing services in the form of online and responsive in receiving incoming data. Behind this there are also inhibiting factors in the process of GODIGI's effective services such as, technical systems in the form of service instability or the system cannot be accessed, full bandwidth capacity, and lack of socialization from the agency to the people of Probolinggo Regency. With the lack of socialization of this GODIGI innovation service, it greatly influences the lack of users of this GODIGI service. From the conclusion of this study, GODIGI online services can simplify the service process of making E-KTP.